Breastfeeding experiences and women's self-concept: Negotiations and dilemmas in the transition to motherhood - Augusto, Amélia; Neves, Dulce Morgado; Henriques, Vera (Frontiers in Sociology, 2023)
Introduction Breastfeeding is much more than a biological event. It is a social construction, full of cultural meanings and framed by social structures. Being, simultaneously, a natural event and a social practice, breastfeeding poses challenges to feminist approaches in the sense it may be acknowledged as an empowering practice for women and/or as a setback in the process of women's social emancipation. Often focused on the product, i.e., the milk and its beneficial properties for the infant's health, the dominant discourse on breastfeeding makes it a trait of good mothering, withdrawing the understanding of the particular (but also structural) contexts in which this practice occurs. Methods Based on results from a focus group with five mothers of a first child, this paper addresses first-person testimonies about breastfeeding and transition to motherhood, aiming to capture eventual self-concept dilemmas, impacts of social judgments, difficulties related to the work-family balance, as well as negotiation processes taking place within couples and early-parents. Results and discussion Despite being subject to tensions and sometimes stressful adaptation processes, motherhood and breastfeeding tend to be ultimately described by women as experiences that enhance welcome changes in personal trajectories, life priorities and identities.